2019
DOI: 10.3390/c5040072
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Carbon Nanomaterials for Biomedical Applications

Abstract: Over the past decade, carbon nanostructures (CNSs) have been widely used in a variety of biomedical applications. Examples are the use of CNSs for drug and protein delivery or in tools to locally dispense nucleic acids to fight tumor affections. CNSs were successfully utilized in diagnostics and in noninvasive and highly sensitive imaging devices thanks to their optical properties in the near infrared region. However, biomedical applications require a complete biocompatibility to avoid adverse reactions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 450 publications
(501 reference statements)
0
28
0
Order By: Relevance
“…It is very well known that electron rich molecules easily form π-π interactions with electron rich molecules and the bonds are very strong. Ce6 is hydrophobic in nature and is an electron rich molecule non-covalently coated with HA-SWCNTs for PDT with the purpose to treat cancer cells [34]. This synthesised nanobiocomposite was physically characterised to confirm the attachments of particles.…”
Section: Discussionmentioning
confidence: 99%
“…It is very well known that electron rich molecules easily form π-π interactions with electron rich molecules and the bonds are very strong. Ce6 is hydrophobic in nature and is an electron rich molecule non-covalently coated with HA-SWCNTs for PDT with the purpose to treat cancer cells [34]. This synthesised nanobiocomposite was physically characterised to confirm the attachments of particles.…”
Section: Discussionmentioning
confidence: 99%
“…After production, graphene can be reformed into zero-dimensional nanomaterial, rolled into one-dimensional nanotube or manipulated into 3D graphite [ 51 ]. Dispersed graphene and graphene oxide (GO) and its interaction with target cells have been explored [ 96 , 97 , 98 ]. Multiple reports have indicated that graphene is an outstanding platform for promoting the adhesion, proliferation and differentiation of different cell types, such as mesenchymal stem cells (MSCs), neural stem cells (NSCs), embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) [ 99 , 100 , 101 , 102 ].…”
Section: Carbon Nanomaterials For Electro-active Scaffoldsmentioning
confidence: 99%
“…Furthermore, graphene cytotoxicity is also closely associated with the biocompatibility of its surface functionalization, non-functionalized counterparts were found to be more toxic [ 122 ]. However, longer term studies need to be conducted, such as preclinical studies considering different animal models [ 96 ].…”
Section: Carbon Nanomaterials For Electro-active Scaffoldsmentioning
confidence: 99%
“…This synthesis method has been a remarkable consideration due to its simplicity and advantage of controlling parameters plus enhanced adhesion. Generally, carbon-based materials are of hydrophobic nature, which can be lessened through decoration with metal nanoparticles via dry synthesis method in an attempt to create bridging of functional groups of supportive nanometal materials (Liu and Speranza 2019). Therefore, the problems associated with wet synthesis procedure have been resolved by dry synthesis approach for preparation of carbon-based materials impregnated with metal nanoparticles.…”
Section: Noncovalent Functionalizationmentioning
confidence: 99%